2017
DOI: 10.1038/srep44246
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Host Cell Protein Dynamics in the Culture Supernatants of Antibody-Producing CHO Cells

Abstract: Chinese hamster ovary (CHO) cells are the most common cell line used for the production of therapeutic proteins including monoclonal antibodies (mAbs). Host cell proteins (HCPs), secreted and released from lysed cells, accumulate extracellularly during the cultures of recombinant CHO (rCHO) cells, potentially impairing product quality. In an effort to maintain good mAb quality during the cultures, HCPs accumulated extracellularly in batch and fed-batch cultures of a mAb-producing rCHO cell line were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 52 publications
2
47
0
Order By: Relevance
“…In most cases, all the proteases mentioned above were identified at a higher concentration in the culture supernatants of fed‐batch cultures than those of batch cultures for both DG‐Fc and DUKX‐Fc cell lines. The same trend was observed for the rCHO‐K1 cell line (Park et al, ). This result suggests that an increased concentration of proteases is in part responsible for the increased degradation of Fc‐fusion proteins.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In most cases, all the proteases mentioned above were identified at a higher concentration in the culture supernatants of fed‐batch cultures than those of batch cultures for both DG‐Fc and DUKX‐Fc cell lines. The same trend was observed for the rCHO‐K1 cell line (Park et al, ). This result suggests that an increased concentration of proteases is in part responsible for the increased degradation of Fc‐fusion proteins.…”
Section: Discussionsupporting
confidence: 82%
“…Among the nine HCPs commonly identified in DG‐Fc and DUKX‐Fc, Ywhae, Lgmn, Prdx1, and Cfl1 were also identified at all sampling times in both batch and fed‐batch cultures of the rCHO‐K1 cell line (Park et al, ). Interestingly, Lyz that is the most abundant HCP in both DG‐Fc and DUKX‐Fc was not identified in the culture supernatants of the rCHO‐K1 cell line (Park et al, ), suggesting that the HCP concentration profiles of rCHO cell lines during culture depend on their CHO host cell lines. These HCPs are secretory proteins located either in the extracellular region or the cytoplasm, indicating that a significant portion of HCPs in the culture supernatants was secreted from viable cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, proteomics analysis of CHO cells undergoing apoptosis during prolonged cultivation or upon transition from exponential to stationary phase resulted in major changes in proteins related to the regulation of stress response, energy metabolism, and cell growth (Carlage et al, 2012;Wei et al, 2011). Complementary results were obtained in proteomics studies of HCPs in conditioned media at the end of batch-and fed-batch CHO cultures and galectin-1 was identified as a marker for early stress in CHO culture supernatants (Park et al, 2017;Woolley & Al-Rubeai, 2009). However, as most studies to date focus on either the cellular or the conditioned media proteome and a particular type of cell death, direct comparison between cellular and conditioned media proteome and different cell death mechanisms is difficult.…”
mentioning
confidence: 97%
“…The organic solvent used here was a 1:1 mixture of methanol and acetone [44][45] . All methods have been previously shown to eliminate detergents from diverse samples [24][25][46][47][48] , and organic solvent precipitation [61][62][63][64] and FASP 56-60 have been previously used to prepare bioreactor supernatant samples for LC-MS/MS proteomics. We found that all three methods could remove the polymer(s) from the samples and that SP3 and S-Trap were better than precipitation ( Fig.…”
Section: Resultsmentioning
confidence: 99%